To Study the Levels of Occupational Stress and Job Satisfaction Experienced By School Teachers: Exploring the Connection Between Occupational Stress and Job Satisfaction in School Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The connection between stress in the workplace and job satisfaction are examine in this research. This study will help school teachers understand the degree of stress and job satisfaction and the empirical results will also help clarify the behavior of school teachers and management of school.Teaching is not a simple activity, because it is a complex mechanism that includes teachers' desire to interact with students, their success in school-related work, receiving interest of knowledge and the opportunity to develop a cordial connection among the colleagues. The whole continuum of teaching, learning, and engagement relies on a teacher’s ability to be fully accepted, and turns the perceived potentialities of a child into actuality. The learning process cannot be practiced in parallel, but it is a successful-directed activity for which teachers ought to provide teaching skills. The instructor is the key person and the success of the educational system relies entirely on the abilities and competencies of the teachers who are relevant in society.